2008
DOI: 10.1124/jpet.108.139204
|View full text |Cite
|
Sign up to set email alerts
|

Positive Modulation of GABAB Receptors Decreased Nicotine Self-Administration and Counteracted Nicotine-Induced Enhancement of Brain Reward Function in Rats

Abstract: Acute administration of ␥-aminobutyric acid (GABA)-B receptor agonists decreases nicotine, cocaine, ethanol, and heroin selfadministration and also decreases food-maintained responding and suppresses locomotor activity at high doses. GABA B receptor-positive modulators may represent potentially improved therapeutic compounds because of their fewer side effects than receptor agonists. The present study investigated the effects of administration of the GABA B receptor-positive modulators 2,6-di- tert-butyl-4-(3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 38 publications
9
81
0
Order By: Relevance
“…GABA B Receptor Ligands and Other GABAergic Drugs. The clinically available and nonscheduled GABA B agonist baclofen only depresses ICSS, and similar effects have been obtained with other GABA B agonists, antagonists, and positive allosteric modulators (Fenton and Liebman, 1982;Macey et al, 2001;Slattery et al, 2005;Paterson et al, 2008;. Other drugs acting at GABA receptors have a more varied profile of effects.…”
Section: Gabaergic Drugsmentioning
confidence: 79%
“…GABA B Receptor Ligands and Other GABAergic Drugs. The clinically available and nonscheduled GABA B agonist baclofen only depresses ICSS, and similar effects have been obtained with other GABA B agonists, antagonists, and positive allosteric modulators (Fenton and Liebman, 1982;Macey et al, 2001;Slattery et al, 2005;Paterson et al, 2008;. Other drugs acting at GABA receptors have a more varied profile of effects.…”
Section: Gabaergic Drugsmentioning
confidence: 79%
“…In vivo results suggest positive GABA B receptor modulators to have anxiolyticand antidepressant-like properties in elevated-maze and forced-swimming tests, respectively (Cryan et al, 2004;Frankowska et al, 2007;Jacobson and Cryan, 2008). In addition, they reduce self-administration of alcohol (Orrù et al, 2005;Liang et al, 2006;Maccioni et al, 2008Maccioni et al, , 2009, cocaine , and nicotine (Mombereau et al, 2007;Paterson et al, 2008). Although these effects are thought to be mediated by positive modulation of GABA B receptors, such modulation has been examined almost exclusively in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, GS39783 completely counteracted nicotine-induced accumulation of ⌬FosB in the nucleus accumbens of these animals. Paterson et al (2008) reported that positive GABA B receptor modulators, similarly to agonists, attenuated the reinforcing and reward-enhancing effects of nicotine. It is noteworthy that in these studies, the effects of GS39783 were observed in a dose range that exactly matched active doses producing the biochemical effects in in vivo microdialysis experiments (Gjoni et al, 2006).…”
Section: F Effects Of Allosteric Gaba B Receptor Modulators Inmentioning
confidence: 99%